The Effect Benson Relaxation Technique With Anxiety In Hemodyalisis Patients In Yogyakarta - Anisa Nuri Kurniasari; Anita Kustanti; Harmilah Harmilah (Universitas Muhammadiyah Yogyakarta, 2016)
ABSTRACTHemodialysis is a treatment that must be done by patients with chronic renal failure. Hemodialysis can changes the various aspects of life of patients, and it cause anxiety. One of the method that can used to reduce anxiety is Benson relaxation techniques. This technique is a combination of relaxation and elements of religious beliefs espoused. To determine the effect of Benson relaxation techniques for anxiety in patients undergoing hemodialysis therapy. Quasi Experiment pre post test design with comparison groups with simple randomization tech- niques conducted, the number of respondents is 30 people were di- vided into intervention group (n = 14) were given relaxation Benson for 2 weeks every day at 6 am and 5 pm and the comparison group (n = 16) were not given the intervention. Anxiety measurements performed twice pretest and posttest with Analog Anxiety Scale (AAS). The average of respondent’s anxiety pre dan post relaxation tecnic Benson in the inter- vention group 21,93 and 13,59. And in the comparison group 17,19 and 12,94. This study showed that there was a significant decrease in anxiety scores in the intervention group p=0.001 (p0.05) and com- parison group p=0,014 (p0,05). The study showed that the interven- tion group obtained a average difference of 8.36, while in the control group obtained a average difference of 4.25 with p value 0.118 (p 0.05). There are no significant differences in the average difference of anxiety in both groups. Benson relaxation techniques have no effect to the de- crease anxiety scores of hemodialysis patients.Keywords: Chronic renal failure, Benson relaxation, Anxiety Analog Scale. ABSTRAKHemodialisis adalah pengobatan yang harus dilakukan oleh pasien dengan gagal ginjal kronis. Hemodialisis dapat mengubah berbagai aspek kehidupan pasien, dan menyebabkan kecemasan. Salah satu metode yang dapat digunakan untuk mengurangi kecemasan adalah teknik relaksasi Benson. Teknik ini merupakan kombinasi relaksasi dan unsur-unsur keyakinan agama yang dianut. Untuk mengetahui pengaruh teknik relaksasi Benson untuk kegelisahan pada pasien yang menjalani terapi hemodialisis. Kuasi eksperimen pra desain post test dengan kelompok perbandingan dengan teknik pengacakan sederhana yang dilakukan, jumlah responden adalah 30 orang yang dibagi menjadi kelompok intervensi (n = 14) diberi relaksasi Benson selama 2 minggu setiap hari pada pukul 6 pagi dan 5 sore dan perbandingan kelompok (n = 16) tidak diberi intervensi. Pengukuran kecemasan dilakukan dua kali pretest dan post test dengan Analog Skala kecemasan (AAS). Rata-rata kecemasan responden pra Dan pasca relaksasi tecnic Benson pada kelompok intervensi 21,93 dan 13,59. Pada kelompok pembanding 17,19 dan 12,94. Studi ini menunjukkan bahwa ada penurunan yang signifikan dalam skor kecemasan pada kelompok intervensi p = 0,001 (p0,05) dan kelompok pembanding p = 0,014 (p 0,05). Studi ini menunjukkan bahwa kelompok intervensi diperoleh perbedaan rata-rata 8,36, sedangkan pada kelompok kontrol diperoleh perbedaan rata-rata 4,25 dengan nilai p 0,118 (p 0,05). Tidak ada perbedaan yang signifikan dalam perbedaan rata-rata kecemasan pada kedua kelompok. teknik relaksasi Benson tidak berpengaruh terhadap nilai penurunan kecemasan pasien hemodialisis.Kata kunci: Gagal ginjal kronis, Benson relaksasi, Kecemasan Analog Scale.